TESTİNG FREQUENCY AND STUDENT ACHİEVEMENT RELATİONSHİP (Third Sector Social Economic Review, 2021)
The main goal of this study was to investigate the testing effect on student achievement in fourth-grade mathematics by using Trends in International Mathematics and Science Study datasets. Another goal of this study was finding out the ideal quiz frequency (daily, weekly, monthly, no quizzes) and student achievement relationship for fourth-grade mathematics course. The study examined this relationship in four selected countries (Korea, England, Turkey, and Egypt) from different achievement levels. The study obtained data from the Trends in International Mathematics and Science Study 2015 exam and from teacher questionnaires. The study utilized multiple linear regressions to find out whether test frequency is a significant predictor of student achievement in all selected countries. Descriptive results of this study showed that quizzing/testing is a widely used tool around the world. In 2015, 99% of 4th graders took at least one test, 16% of students took tests every day, and only 1% of them did not take any tests. Regression results indicated that testing frequency improved student achievement. This improvement is significant in Korea and Turkey, but not significant in England and Egypt.
Keywords: Testing Frequency; Testing Effect; Student Achievement; Mathematics